2001
DOI: 10.1248/bpb.24.925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexamethasone Palmitate-Low Density Lipoprotein Complex on Cholesterol Ester Accumulation in Aorta of Atherogenic Model Mice.

Abstract: In order to confirm the efficacy of dexamethasone palmitate (DP)-low density lipoprotein (LDL) complex on experimental atherosclerosis in vivo, we examined whether DP-LDL complex could be effective for cholesterol ester accumulation in the aorta of atherogenic mice. Nonatherogenic and atherogenic mice were fed with normal and atherogenic diet for 14 weeks, respectively. Dexamethasone (DEX), lipid emulsion containing DP (DP-LE), or DP-LDL complex was intravenously injected once a week from 8 to 14 weeks. Choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…It has been shown that exogenous glucocorticoids are associated with impaired cholinergic vasodilatation via disturbances in endothelial nitric oxide system [28]. However, it must be noted that studies in animals have shown the atheroprotective effects of medium-term glucocorticoid receptor agonist therapy in mice [29] and rabbits [30]. The data regarding cardiovascular risk in both Cushing Syndrome and sCS emphasized the role of metabolic disturbances [5,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that exogenous glucocorticoids are associated with impaired cholinergic vasodilatation via disturbances in endothelial nitric oxide system [28]. However, it must be noted that studies in animals have shown the atheroprotective effects of medium-term glucocorticoid receptor agonist therapy in mice [29] and rabbits [30]. The data regarding cardiovascular risk in both Cushing Syndrome and sCS emphasized the role of metabolic disturbances [5,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the systemic effects of glucocorticoids on cardiovascular risk factors (glucose, insulin, lipids and blood pressure) may offset beneficial effects within the vessel wall. Dexamethasone reduces cholesterol ester accumulation in the aorta [133], and glucocorticoids (dexamethasone, hydrocortisone) inhibit neointimal lesion formation in rats [134,135], rabbits [136][137][138] and dogs [139] (with a few contradictory reports [140,141]). Clinical trials in humans, by contrast, have proved disappointing (with notable exceptions [130]): methylprednisolone did not inhibit restenosis after coronary angioplasty [142] or stent implantation [143], whilst the combination of a glucocor-570 P. W. F. Hadoke et al Intra-vascular glucocorticoid metabolism ticoid with colchicine increased the risk of coronary aneurysm following stent placement [144].…”
Section: Neointimal Proliferationmentioning
confidence: 99%
“…[1][2][3][4] Because of its insolubility in water and thus relatively low bioavailability by oral administration, research on the drug delivery system of dexamethasone palmitate has raised many interests. Liposomes, closed bilayer vesicles with around 100 nm in diameter, formed by the distribution of lipid and cholesterol in water, have a positive effect on body's drug absorption because of their similarity and compatibility with cell membrane.…”
Section: Introductionmentioning
confidence: 99%